مشكلات تعليم النحو لدى طلاب الدفعة 21 ج بقسم تعليم اللغة العربية في جامعة أنتساري الإسلامية الحكومية بنجرماسين - Azima, Huwaida Naila; Qomariah, Rafi'atun Najah; Mahfuzah, Noor (STIT Darul Hijrah Martapura, 2024)
ABSTRACT This research aims to identify the challenges faced in the process of learning nahwu (Arabic grammar), which lead to low student achievement. The study adopts a qualitative descriptive method, involving students from the 2021 cohort of the Arabic Language Education Department at UIN Antasari Banjarmasin as research participants. The results reveal that students encounter linguistic difficulties in understanding word form changes (i'rab) and applying grammatical rules practically. On the non-linguistic side, the decline in student interest is attributed to monotonous teaching methods and a lack of interaction during the learning process. The research recommends employing innovative and interactive methods to motivate students and enhance their understanding of nahwu.Keyword: Educational problems, teaching grammar, teaching Arabic language. مستخلص البحثيهدف هذا البحث إلى تواجه عملية تعلم النحو العديد من التحديات التي تؤدي إلى تدني نتائج تعلم الطلاب. اعتمد هذا البحث على المنهج الوصفي النوعي بمشاركة طلاب الدفعة 2021 ج قسم تعليم اللغة العربية بجامعة أنتساري الإسلامية الحكومية بنجرماسين كعينة للبحث. وأظهرت نتائج البحث أن الطلاب يواجهون صعوبات لغوية في فهم تغيرات أشكال الكلمات (الإعراب) وتطبيق قواعد النحو بشكل عملي. ومن الجانب غير اللغوي، يعود تدني اهتمام الطلاب إلى الطرق التعليمية الرتيبة وقلة التفاعل في العملية التعليمية. يوصي البحث باستخدام أساليب مبتكرة وتفاعلية لتحفيز الطلاب وزيادة فهمهم في تعلم علم النحو.الكلمات المفتاحية: مشكلات التعليم، تعليم النحو، تعليم اللغة العربية.